Back to Von Thunen: a Southern European perspective on mono-centric urban growth, economic structure and non-urban land decline*. Issue 3 (3rd July 2017) - Colantoni, Andrea; Grigoriadis, Efstathios; Sateriano, Adele; Sarantakou, Efthymia; Salvati, Luca
ABSTRACT: This study assesses trends (1960–2010) in forest cover over a Mediterranean metropolitan region (Attica, Greece) with the aim to investigate the role of local contexts promoting changes in the use of land. Forest cover decreased in a spatially heterogeneous manner over the study period determining a land-use structure coherent with the Von Thunen mono-centric model. We used a multivariate exploratory analysis of 26 contextual variables to identify changes in the urban spatial structure at the local scale. The shift from a land-use structure based on urban–rural and cropland-forest polarizations in the early 1960s to a pattern based on the polarization in medium-density, mixed urban/agricultural areas and low-density, sparse forest land has been observed in the last 50 years. Urban expansion into rural land and the establishment of protected areas in economically marginal and remote districts has been identified as relevant drivers of landscape transformation in the area. Our study demonstrates that land-use changes driven by expansion of dispersed settlements may consolidate mono-centric urban structures. A concentric land-use distribution around the central city is compatible with urban sprawl and may be indirectly supported by 'green belt' regional planning and environmental policies protecting high-quality natural land.